Teachers Turnover Intention: The Role Of Work Motivation, Job Stress, And Organisational Commitment - Azkiya Banata; Nurmala Katrina Pandjaitan; Amir Tengku Ramly (Ridwan Institute, 2023)
The phenomenon of teacher decline happens in all stages of education in 2021/2022. Continuous situations would hinder the school's objectives, cause a drop in academic achievements, and disrupt the talent management process during the leadership turnover among others. Teacher turnover can be predicted through turnover intention, which can be affected by work motivation, job stress, and organizational commitment. This research aims to determine the effect of work motivation on job stress, organizational commitment, and turnover intention and the impact of job stress and organizational commitment on turnover intention. This research was conducted in SMA (senior high school) and SMK (vocational school) PKP Jakarta Islamic School, which involved 77 respondents, from March 2022 to June 2023. SEM-PLS is used to process and evaluate the research hypotheses. The results show work motivation does affect job stress, organizational commitment, and turnover intention, and job stress and organizational commitment do affect teacher turnover intention.